Potential impacts of climate change on the distribution of the Yellow-spotted mountain newt Neurergus derjugini (Nesterov, 1916) - Maryam Malekoutian; Mozafar Sharifi; Somaye Vaissi (علوم محیطی)
Introduction: Climate change is recognized as one of the largest threats to biodiversity and is expected to result in shifting species distributions and increasing extinction risk of populations that are unable to adapt or relocate to suitable habitats. In the present study, habitat suitability of the yellow-spotted mountain newt was modeled to identify the current suitable habitats, to predict the expansion or contraction of the distribution of the species under future climate change scenarios, and to determine the main environmental variables. Material and methods: The studied species inhabit 57 highland streams of the Zagros Mountain range in western Iran and eastern Iraq. In the present study, species distributions were examined using the maximum entropy model (MaxEnt) for the current and the future (2050 and 2070) climate projection under two optimistic (RCP2.6) and pessimistic (RCP8.5) scenarios. Results and discussion: Based on the results, precipitation of the coldest quarter (BIO13) was the most percent of contribution to predicting species distribution. Comparison of suitable habitat areas in the current and future climate conditions showed that suitable habitats area for the species will not significantly decrease under the optimistic (RCP2.6) scenario in 2070 and an increase was also observed in 2050. Although, a reduction in suitable habitats area (more than 50%) was observed in 2070 under pessimistic (RCP8.5) scenarios. The results of the model supported the hypothesis that due to future climate change, the species distribution range is likely to be conserved in the refugia located in the center and south of the distribution range and by shifting to higher altitudes. Conclusion: Results obtained from the current study supported the hypothesis that the Zagros climatic refugia play an important role in conserving populations as well as habitats suitable for the Yellow-spotted mountain newtduring climate change.